ISSUES AND CHALLENGES IN NIGERIA- NIGER REPUBLIC BORDER SECURITY - Muslim, Arzika (International Journal of Research -GRANTHAALAYAH, 2023)
This is an open border where contact is predominant and does not function as barrier between the two countries. It is a unique zone of cultural similarities, language, law as well as condition of trade, work, and life. This border is the location for the most intense interactions between the two populations. The border has the highest level of cross-border movement of border residents. Security challenge across this border is attributed to a constant movement of people and goods. This paper is on the issues and challenges of security and social stability along Nigeria-Niger Republic International border. It argues that amongst the various challenges to border security and social stability along the border, corruption, insecurity, porous nature of the border and uncontrollable movement of people are responsible. The persistence of these grim issues makes the border tumbled pathway to heightened state of insecurity and social instability across the border. This is in view of the numerous activities taking place across this border posing security threat. The paper employs reactive re-active model approach as a variant of linkage theory as a tool in understanding the study. Qualitative method was employed for this study. The paper concludes and recommends the study.